Relevance of Citizens’ Mediation Centre in Resolution of Landlord-Tenant Dispute, in Lagos State, Nigeria - Amos Ojo ADEDEJI (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
The inadequacy of the housing needs for the teaming population of Lagos has made house rental key feature in the State. This has made Landlord-tenant relationships suspicious and mistrust hence, dispute. To address the ugly trend, Lagos State established Citizens’ Mediation Centre which was expected to achieve peaceful co-existence, and aid in continuation of housing business. The study quantitatively and qualitatively examines the relevance of Citizens’ Mediation Centre in resolution of landlord-tenant dispute. The study adopts Human needs theory as its theoretical framework. The finding revealed that the intervention of the centre has reduced court backlog. The study identified inadequate publicity, lack of sufficient and skilled staff and financial paucity among many other factors hindering the efficiency of the centre. It recommended adequate publicity, audience target, and appropriate and adequate training for staff, among others, as ways to enhance the functions of the Centre and improve its efficiency in resolving landlord-tenant disputes in Lagos State. The state will experience more social stability, peaceful co-existence between landlords and tenants which will invariably lead to social-economic development by putting in practice the recommendations highlighted.